MSME RETAIL TRANSFORMATION STRATEGY BASED ON SHARIA ECONOMIC PRINCIPLES - Sugina Mr; Ahmad Sarmadi; Dedy Iskandar; Andri Cahyo Purnomo (EKOSSISTEM : Islamic Economics, Banking, Law, System, 2026)
The digital transformation of shariah-based retail MSMEs is a strategic effort to enhance competitiveness and ethical business value in the digital era. However, its implementation still faces fundamental challenges such as symbolic tendencies, limitations in digital and shariah literacy, infrastructure gaps, and non-inclusive access to financing. This study aims to analyze the digital transformation of retail MSMEs within the framework of shariah economics using a qualitative approach based on literature review. Data were collected from various selected secondary sources to examine relevant characteristics, challenges, opportunities, and strategies. The findings indicate that the digital transformation of MSMEs is a complex, holistic process, where internal limitations of MSMEs (such as capital and human resources) intersect with external challenges in the form of uneven digital infrastructure, low literacy, and suboptimal regulatory frameworks. On the other hand, shariah principles and the presence of shariah fintech actually offer significant opportunities to build a more just and sustainable financial system. However, there exists a fundamental paradox in the form of a wide gap between available technological innovations and the adoption capacity of business actors. Therefore, effective transformation strategies must focus on building a symbiotic ecosystem through synergistic collaboration among all stakeholders.